Foreign direct investment and local supplier upgrading – the case of grocery retail in Turkey. Issue 2 (3rd July 2019) - Gersch, Inka
ABSTRACT: Foreign direct investments (FDIs) are noted as an important cross-border channel for knowledge. Thus, expanding companies can contribute to local supplying companies' capability development, an important precondition for upgrading processes. Several transnational grocery retailers have expanded globally and introduced modern supply chain management practices to markets of emerging and developing countries. However, agri-food industries are under-researched regarding FDI-induced knowledge transfer and supplier upgrading. Based on qualitative interviews with both retailers and suppliers in the emerging market of Turkey, this article discusses the upgrading processes of fresh food suppliers driven by the FDI of grocery retailers. This article shows how the foreign retailers' fresh fruit and vegetable supply structures have evolved towards the preferences of suppliers that vertically integrate value chain functions. Within this dynamic, transnational retailers proactively shape their suppliers and promote (functional) upgrading. The findings imply that (1) local regulatory environments should foster local sourcing and (2) the way for suppliers to work towards a solid value chain positioning is to fully integrate supply chain functions including agricultural primary production. This article argues that integrating low value-adding functions can be a type of functional upgrading that has not yet been acknowledged.